Nutrition and ethics: A catalyst for social transformation and personal identity - Karaboue, Michele (Progress in Nutrition, 2024)
This study delves into the multifaceted relationship between humans and food considering its profound ethical, cultural, and bioethical implications. It challenges the reductionist view of food as just a material object for satisfying basic needs, advocating for a recognition of its symbolic and value-laden significance that transcends mere survival. Food is depicted as a pivotal element in human history, culture, and social organization, acting as a bridge that fosters dialogue, understanding, and connection across generations and cultures. The discussion extends to the ethical dimensions of dietary practices, seeing them as expressions of identity, tradition, and cultural heritage that contribute to shaping societal norms, values, and relationships.